ISLAM IN SPIRITUAL AND RELIGIOUS GLOBALIZATION: PERFORMANCE AND PLACE IN THE WORLD - Abuov Amrekul (Academic Journal of Physical and Chemical Sciences, 2020)
The rise of religiosity and religious warfare today should alert us to an indisputable fact: when a state does not respond to people's basic needs, rights and beliefs, the citizens of these states seek help and security from other similar options. The two leading indicators of a sovereign state are religious and cultural similarities in times of crisis, which appear, first of all, in two powerful forces - Islamism and ethnicity. However, despite their profound authenticity and “eternal” proof, of course, neither religion nor any other similarity can replace a reliable system of government. In today's urbanized and globalized Muslim world, religious and cultural similarities cannot take their rightful place apart from the role of the state. In a complex and rapidly changing worldview, world religions play a dual and contradictory role: on the one hand, they are a kind of catalyst for extremism, violence and political vulgarity, on the other hand, they characterize the defining concepts of morality and behavior, justice, harmony, equality and charity. gives. If the modern state performs its function effectively and fairly, religion will tend to retreat to certain spheres of society as late as possible. On the contrary, people experience the fear of internal violence, they see religion as the last resort, and they turn to the restoration of justice and hope for a brighter future.